High-efficiency formation of influenza virus transfectants. - Enami, M (1991)
cDNA-derived RNAs were introduced into the genomes of influenza viruses by using an improved ribonucleoprotein (RNP) transfection protocol. Up to 10(5) viral transfectants with a novel neuraminidase gene could be obtained by using a 35-mm dish (10(6) cells) for RNP transfection. In addition to genes coding for surface proteins (hemagglutinin and neuraminidase), we also exchanged a gene coding for nonsurface proteins. The cDNA-derived influenza A/PR/8/34 virus NS gene was introduced into a temperature-sensitive mutant with a defect in this gene. We suggest that the term influenza virus transfectant be used for those viruses which are made by RNP transfection with cDNA-derived RNA.